Rumours, Ruffians, and the U.S.-Upper Canada Border: Patriots, Publishers, and Hunters Respond to the Upper Canadian Rebellion and Patriot War, 1837-1841 - Steedman, Josh (Ontario History)

(untitled) (The Ontario Historical Society, 2023)
This article surveys the history of the American social and political reaction to the events surrounding the Upper Canadian Rebellion. It focuses on the efforts of Michiganders and members of secret societies who supported the rebellion and Patriot War and on their experiences of engaging in revolutionary activities. By engaging with an enemy abroad, whether real, or imagined, these Americans sought a panacea to ease their generational and nationalistic angst. In return, they believed that liberating Canadians from British tyranny would cement their legacies in American history. This heroism, coupled with the formation of a secret society, the Hunters’ Lodges, temporarily distracted these Americans as well as some government officials from economic hardship, domestic and political turmoil, and perhaps most importantly, a rapidly changing world.